Regional differences and improvement potential of carbon emission efficiency in China’s power industry: insights from meta-frontier DEA model considering integer constraints - Huang, Xiang; Zhao, Ruizeng (Frontiers in Energy Research, 2024)
Previous studies on the carbon emission efficiency (CEE) in the power industry have neglected concerns related to regional heterogeneity and the integer character of certain indicators. In response to these issues, this study proposes a meta-frontier DEA model that integrates integer constraints for evaluating the CEE of China’s provincial power industry from 2011 to 2021. This study also proposes to apply the Theil, technology gap ratio, and inefficiency decomposition indexes to analyze regional disparities, technological gaps, and strategies for enhancing CEE within China’s provincial power industry. The research findings highlight several key points. First, China’s power industry exhibits inefficiencies in CEE. The central region mainly contributes to the overall CEE decline, and approximately 70% of provinces demonstrate an average CEE below 0.70. Second, the technological level of the western region is leading, while that of the central region is the worst. Specifically, Ningxia, Hainan, and Jiangsu have the most advanced production technology levels. Third, substantial disparities in CEE within China’s power industry primarily stem from regional imbalances in development. Fourth, technical inefficiency contributed 68.24% of the CEE in the central region, and management inefficiency contributed 96.91% and 65.42% in the western and eastern regions, respectively. Overall, China’s power industry still has 37% potential for improvement.